Association of Amniotic Fluid Index (AFI) with Maternal and Perinatal Complications in Premature Rupture of Membranes - Khan, Sadia; Shetu, Shain Fariya; Chowdhury, Mushrefa; Sarker, Afsana; Khan, Ashfaque Rahman (Journal of Rangpur Medical College, 2025)
Background: Premature rupture of membranes (PROM) at term complicates 8–10% of pregnancies and increases the risk of maternal and perinatal complications. Amniotic fluid index (AFI), a key indicator of fetal well-being, may influence delivery outcomes in PROM cases. Objective: The study evaluated the association between AFI levels and maternal-neonatal complications in term PROM patients. Methods: The prospective observational study included 126 pregnant women with the term PROM, grouped into two categories based on AFI values: Group A (AFI >5cm, n=76) and Group B (AFI <5cm, n=50). Latency period, mode of onset of labour, type of delivery, and maternal and neonatal complications were followed up in the participants. Results: Both groups had comparable demographic characteristics and latency duration. Group B (AFI <5cm) exhibited a significantly greater rate of labour induction (80% vs 52.6%, p=0.001) and caesarian section (86% vs 50%, p=0.002). Maternal and neonatal complications occurred significantly more often in Group B (62% vs 7.9%, p<0.001) and (62% vs 0.03%, p<0.001) respectively. Conclusion: In PROM patients, oligohydramnios (AFI <5cm) is significantly associated with augmented labour induction, caesarian delivery, and maternal and neonatal complications. J Rang Med Col. 2025 Sep;10(2): 49-54